BENTUK PENYAJIAN GENDANG BELEQ GUNTUR TLU DESA SONGAK KECAMATAN SAKRA LOMBOK TIMUR NTB - Rohin, Wiwin Familia (TAMUMATRA, 2019)
This study aims to describe the form of serving gendang beleq guntur tlu Songak village, Sakra Lotim district, NTB. This research was also conducted because this music is a traditional art that is in Songak village which must be preserved,one of the ways is to do this research.             The approach used in this research is descriptive qualitative. The object in this study is gendang beleq guntur tlu which includes the presentation form. The subjects in this study were supporters of gendang beleq guntur tlu itself. The study focused on the form of gendang beleq gutur tlu. Data collection by(1) Observation, (2) interviews and (3) documentation. Data is done by (1) data reduction, (2) data presentation, (3) conclusion. To check the validity of the data, the data validity technique is used by triangulation technique.            From the results of the study, it has been found about: (1) The form of the presentation gendang beleq guntur tlu is a form of dance orchestra music using various traditional musical instruments and covers. Gendang Beleq Guntur Tlu itself. b. Performance (performance) c. Performance procedures d. floor pattern.   e. dance f. place of show g. cosmetology h. fashion and i. music. (3) Musical instruments used by gendang beleq, petuk, cemprang / ceng-ceng, reong, gong,oncer.